2010
DOI: 10.3892/ijmm_00000357
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter wave treatment inhibits NO-induced apoptosis of chondrocytes through the p38MAPK pathway

Abstract: Abstract. In the present study, we investigated the effects of millimeter wave treatment on the activation of the p38MAPK signaling pathway in the process of NO-induced apoptosis in chondrocytes. Cartilage was isolated from the knee joint of SD rats and used to establish cultured primary chondrocytes. After identification using in situ staining of type II collagen, the passage 2 chondrocytes were incubated with or without sodium nitroprussiate (SNP) to induce apoptosis and treated with a millimeter wave for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…As a physical therapeutic regimen, millimeter wave treatment differs from conventional medical regimens in its convenience, safety and non-invasiveness. Our pilot study previously demonstrated that millimeter wave treatment down-regulated the expression and activation of P-p38 and p53 in apoptotic chondrocytes and suppressed the activity of caspase-3, a key player in chondrocytic apoptosis, thus leading to the inhibition of chondrocytic apoptosis (14). As a rapidly responding nuclear transcription factor, a large amount of NF-κB is involved in cell proliferation and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…As a physical therapeutic regimen, millimeter wave treatment differs from conventional medical regimens in its convenience, safety and non-invasiveness. Our pilot study previously demonstrated that millimeter wave treatment down-regulated the expression and activation of P-p38 and p53 in apoptotic chondrocytes and suppressed the activity of caspase-3, a key player in chondrocytic apoptosis, thus leading to the inhibition of chondrocytic apoptosis (14). As a rapidly responding nuclear transcription factor, a large amount of NF-κB is involved in cell proliferation and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter wave is a high-frequency electromagnetic wave at a wavelength from 1-10 mm and a frequency of 300 million cycles/sec (300 MHz) to 300 billion cycles/second (300 GHz) (10,11). The millimeter waves within living organisms generate 0.5x10 10 -3x10 12 coherent oscillations during metabolism, which can be absorbed by biological tissues through resonance to produce a non-thermal biological effect (12).…”
Section: Introductionmentioning
confidence: 99%
“…This cell type is responsible for repairing damaged cartilage tissue. We previously demonstrated that chondrocytes are obtained by mechanical and chemical isolation methods and that the purity of the isolated chondrocytes is high (14,21). This process provides allowed for the investigation of the effect of MW on chondrocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…MW has been shown to evoke multiple biological effects and is beneficial in the treatment of OA. Recently, we reported that MW inhibited sodium nitroprussiate (SNP)-induced apoptosis of chondrocytes (14). To further explore MW as a potential therapeutic agent in OA, the effect of MW on the mitochondrion-dependent apoptotic pathway in chondrocytes was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation